Employee Retention in Nepalese Commercial Banks - Chalise, Dhan Raj (Management Dynamics, 2019)
Employee retention issues is the burning issues especially in the banking sector in Nepal. This study is designed to examine the factors on retention of employees in Nepalese commercial bank. Adopting descriptive cum analytical research design the study is based on 5 point likert scale questionnaire. 200 managers, assistant manager and officers level employees from three commercial bank operating at Kathmandu valley were selected on basis of stratified random sampling method. Training and Development, Career Opportunity and Work Lifer policies are taken as dependent and Employee retention as an Independent variable of the Study. The collected data were analyzed through correlation, regression and coefficient analysis to establish the relationship between the dependent and independent variables. The result showed a significant positive relationship between career opportunities, work life policy with employee retention. In addition this study replicates the high level of effect of work life policy and no significant relationship with training and development program in Nepalese commercial banks.